CHALLENGES OF SANSKRIT TEACHING IN INDIA - Kavita Sharma, Dr Shyamveer Ghuraiya, Dr Manisha Gurjar, Dr. Charu Mehandiratta (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2016)
The ancient and classical creations of the Indo-Aryan tongue each in quality and in body and abundance of excellence, in their potent originality and force and sweetness, in their substance and art and structure, in grandeur and justice and charm of speech and at intervals the peak and breadth of the reach of their spirit stand very plain at intervals the front rank among the world's nicest literatures. The language itself, as has been universally recognized by those competent to make a judgment, is one among the foremost good, the foremost glorious and splendidly spare literary instruments developed by the human mind, quickly majestic and sweet and versatile, durable and clearly-formed and full and spirited and delicate, and its quality and character would be of itself a spare proof of the character and quality of the race whose mind it expressed and additionally the culture of that it had been the reflective medium. Keywords-Sanskrit,Challenges,opportunities,India